A guide to support Australian university teaching and learning centres in strategic leadership for teaching and learning enhancement. - Holt, Dale (Australian Learning & Teaching Council, 2010)
This is a guide to assist teaching and learning centre leaders and staff members engage in a productive strategic leadership development program to enhance long-term performance. The guide will support leadership in framing perspectives, activities and actions in relation to enhanced strategic leadership. It will be of interest to all staff in universities who carry teaching and learning leadership and management responsibilities. The program can be used as part of internal and external centre reviews, or as part of a centre's commitment to ongoing quality assurance and continuous quality improvement. [p.1, ed]